2015
DOI: 10.1177/0145445515601793
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychological Distress, Negative Cognitions, and Expectancies on Problem Drinking

Abstract: Few studies have sought to understand the concurrent relationship between cognitive and affective processes on alcohol use and negative alcohol-related consequences, despite both being identified as predictive risk factors in the college population. More research is needed to understand the relationships between identified factors of problem drinking among this at-risk population. The purpose of this study was to test if the relationship between psychological distress and problem drinking among university stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
5
0
1
Order By: Relevance
“…These psychological trait associations seem to indicate that a protective allele for alcohol use behaviors is generally associated with positive psychological circumstances. A consistent epidemiological literature has shown that alcohol use and abuse are associated with psychological distress (Ibanez et al, 2015;Obasi et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…These psychological trait associations seem to indicate that a protective allele for alcohol use behaviors is generally associated with positive psychological circumstances. A consistent epidemiological literature has shown that alcohol use and abuse are associated with psychological distress (Ibanez et al, 2015;Obasi et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…However, anxiety symptoms alone do not necessarily lead to an increased urge to drink immediately in non-alcohol naïve adolescents ( Blumenthal et al, 2015 ), indicating that there are other factors at play in the relationship between adolescent alcohol consumption and anxiety that require further study (with access to alcohol likely being relevant). The same must be said of other common comorbidities of AUD, including MDD and conduct disorder due to the tendency to use alcohol as a coping method for psychological distress ( Zaso et al, 2021 ) and as a negative reinforcer among late-stage adolescents ( Obasi et al, 2016 ). Obasi et al (2016) surveyed a population of undergraduate college students, examining the relationship between psychological stress and alcohol use, and report the relationship between individuals with problem drinking (as assessed by the Alcohol Use Disorders Identification Test) positively correlates with poor emotional coping skills, depression, anxiety, and positive alcohol related expectancies.…”
Section: Relationship Between Stress and Alcohol Usementioning
confidence: 99%
“…The same must be said of other common comorbidities of AUD, including MDD and conduct disorder due to the tendency to use alcohol as a coping method for psychological distress ( Zaso et al, 2021 ) and as a negative reinforcer among late-stage adolescents ( Obasi et al, 2016 ). Obasi et al (2016) surveyed a population of undergraduate college students, examining the relationship between psychological stress and alcohol use, and report the relationship between individuals with problem drinking (as assessed by the Alcohol Use Disorders Identification Test) positively correlates with poor emotional coping skills, depression, anxiety, and positive alcohol related expectancies. A model fit was able to predict that the relationship between depression and anxiety and alcohol use is mediated by a chain of negative affect regulation and positive alcohol expectancies ( Obasi et al, 2016 ).…”
Section: Relationship Between Stress and Alcohol Usementioning
confidence: 99%
See 1 more Smart Citation
“…Una de las principales hipótesis que se han propuesto para la explicación de esta comorbilidad entre depresión y abuso de sustancia, es la hipótesis de automedicación (self-medication hypothesis; Gómez-Coronado, et al, 2018). Se afirma que los componentes cognitivos de la depresión, como ser los pensamientos de fracaso, o de disconformidad con uno mismo, amplificarían la afectividad negativa, siendo el consumo una forma conductual de regulación emocional que buscaría aminorar dicha afectividad (Obasi, Brooks, y Cavanagh, 2016). Esta hipótesis es coincidente con el Modelo de Cascada Emocional (Emotional Cascade Model; Selby, Anestis, y Joiner, 2008;Selby, Franklin, Carson-Wong, y Rizvi, 2013) así como los modelos transdiagnósticos de la regulación emocional (Sloan, et a., 2017), en donde se indica que ciertas respuestas o contenidos cognitivas generan un incremento de la afectividad negativa, a partir de lo cual personas que no posen otros recursos más apropiados recurren a modos de afrontamiento maladaptativos, como ser el consumo de sustancia, con el objeto de disminuir este estado afectivo negativo.…”
Section: Introductionunclassified